(untitled) (Baghdad Science Journal, 2014)
In this study, we design narrow band pass filter for window (3_5) ?m dependent on the needle optimization method , and a comparison with global designs published -Also, the effect of change parameter design on the optical performance of filter was studded and being able to overcome the difficulties of the design.In this study, the adoption of homogeneous optical properties materials as thin film depositing on a substrate of germanium at wavelength design (? = 4 ?m). For design this kind of filters we used advanced computer program (Matlab )to build a model design dependent both matrix characteristic and Needle technique. In this paper we refer to the type of Mert function , which is used for correct optical performance access to the target in very short time.